Aplicabilidade do princípio constitucional da proteção do Consumidor aos contratos eletrônicos - Carneiro, Ligia Maria Cavalcante (2008)
The applicability of the constitutional principle of consumer protection is indicated here as the main solution to fill the legal gap concerning the new electronic contracts. From an unknown and irrelevant precept in the consumption relationships developed during the Liberal State, to a leading factor for the economical activity of the Social and Constitutional State of Right, the constitutional principle of consumer protection walked a long hard path before being reconized and valued, bringing to the extent of consumption relationships the desired placement of a vulnerable consumer in the same level as the businesses that sell goods and services, through protective norms. According to this, The Federal Constitution of 1988 took the consumer protection as one of its icons, including it in the fundamental rights and guarantees and, like one of them, a self-aplicable right, with immediate normative power, in spite of the determination of preparation of the Protection Code, which made it stronger, rulling all developed peculiarities in the consumption relationships so far. With the globalization and one of its most interesting features, the internet, a new stage in the consumption relationships began, as well in the international business: The e-commerce was launched, what, in a chaotic but self-organized way, developed a new comfortable layout for the comsumption relationships, when by a simple mouse click, it is possible to reach any kind of goods or services, from national or international businesses, through their virtual shops. However, although it is just a new way of bringing into effect traditional legal contracts, since they are made through electronic support, a lot of doubts and questions related to the regulation of their main aspects have been coming up, for there is not a whole effective national norm, which has been restricting the practice of consumption relationships due to the remaining suspicion about the way they are done. In this case, it is summoned the normative power of the constitucional principle of consumer protection, displayed in the Federal Constitution of 1988, and, as well, in the other Constitutions of all democratic countries, which values highly the consumer citizen protection and their dignity. Due to the nonexistence, and even the difficulties in preparing a harmonic norm which reaches the national and international e-commerce, it is vented the invocation of this normative power as guidelines for solving the increasing demand coming around the Judicial Power related to this new contract perspective through the matrix.